2009
DOI: 10.1088/0004-6256/137/2/3245
|View full text |Cite
|
Sign up to set email alerts
|

Starmind: A Fuzzy Logic Knowledge-Based System for the Automated Classification of Stars in the Mk System

Abstract: Astrophysics is evolving toward a more rational use of costly observational data by intelligently exploiting the large terrestrial and spatial astronomical databases. In this paper, we present a study showing the suitability of an expert system to perform the classification of stellar spectra in the Morgan and Keenan (MK) system. Using the formalism of artificial intelligence for the development of such a system, we propose a rules' base that contains classification criteria and confidence grades, all integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…They found that only ANNs could equal the human expert precision. Manteiga et al (2009) used ANNs and fuzzy reasoning to classify stellar spectra. The precision they reach in A&A 538, A76 (2012) spectral classification is similar to that of human experts in more than 80% of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…They found that only ANNs could equal the human expert precision. Manteiga et al (2009) used ANNs and fuzzy reasoning to classify stellar spectra. The precision they reach in A&A 538, A76 (2012) spectral classification is similar to that of human experts in more than 80% of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…In the probabilistic mode of classification, they obtained an error of 2.09 subclasses. Manteiga et al (2009) proposed a classifier, STARMIND, which tries to mimic the human reasoning for stellar classification by using a knowledge base comprising of spectral features computed from template spectra. The authors deployed an expert system (ES) which uses this knowledge base and applies fuzzy logic for classifying spectra with an overall accuracy of 82.7% at the main-class level.…”
Section: Introductionmentioning
confidence: 99%
“…are only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/612/A98 Numerous works have been done that explore the performance of the automatic MK classification of spectra (see e.g. Bailer-Jones et al 1998;Singh et al 1998;Bailer-Jones 2002;Rodríguez et al 2004;Giridhar et al 2006;Manteiga et al 2009;Navarro et al 2012). The main approach followed in these works was to apply supervised learning training using labelled data.…”
Section: Introductionmentioning
confidence: 99%